Inequality in Mexico: Labour markets and fiscal redistribution 1989-2014 - Raymundo M. Campos Vázquez; Nora Lustig; John Scott (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Income inequality in Mexico increased between 1989 and 1994; between 1994 and 2006, inequality declined; and, between 2006 and 2014, inequality was again on the rise. We apply decomposition techniques to analyse the proximate determinants of labour income inequality and fiscal incidence analysis to estimate the first-order effects of taxes and social spending on the distribution of income. The key component that underlies the "rise-decline-rise again" pattern was the evolution of returns to skills. In addition, while changes in fiscal policy in the 1990s were progressive and pro-poor, the redistributive effect has declined significantly since 2010, as transfers have become less progressive and net indirect taxes have increased.
Keywords: D30; H39; I30; J20; J31; O54; 330; labour income; inequality; top incomes; poverty; fiscal redistribution; Mexico